2005
DOI: 10.1542/peds.2005-0219
|View full text |Cite
|
Sign up to set email alerts
|

Recent Steroid Therapy Increases Severity of Varicella Infections in Children With Acute Lymphoblastic Leukemia

Abstract: ABSTRACT. Objective. The varicella-zoster virus (VZV) continues to be a dangerous pathogen to immunocompromised children. Children with acute lymphoblastic leukemia (ALL) are treated with intermittent steroid therapy. This study was undertaken to examine the relationship between steroid therapy for ALL and severity of varicella infection.Methods. We performed a retrospective review of patients who were on Pediatric Oncology Group Protocol 9201 and had a history of varicella infection. Pediatric Oncology Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 27 publications
0
31
1
Order By: Relevance
“…51 The use of systemic corticosteroid appears to substantially increase the risk of severe or fatal varicella. 52,53 After SCT, the risk of varicella is highest in the first 24 months, or beyond this time if undergoing immunosuppressive therapy and/or having chronic GVHD.…”
Section: Varicella-zoster Virus (Vzv)mentioning
confidence: 99%
“…51 The use of systemic corticosteroid appears to substantially increase the risk of severe or fatal varicella. 52,53 After SCT, the risk of varicella is highest in the first 24 months, or beyond this time if undergoing immunosuppressive therapy and/or having chronic GVHD.…”
Section: Varicella-zoster Virus (Vzv)mentioning
confidence: 99%
“…A detailed review of all 110 cases of varicella on this protocol found that more severe infections were seen in patients who received prednisone near the time of the varicella infection. 20 …”
Section: Deaths In Remissionmentioning
confidence: 99%
“…Further circumstantial evidence implicating PBX/HOX involvement in VZV pathogenesis is the extremely well documented association between severe disseminated visceral VZV infection and patients with HOX-expressing leukemias (26). In addition, severe VZV disease is seen in bone marrow transplant recipients (5), patients who often receive corticosteroid treatment (16). Even more suggestive are the peculiar features associated with congenital varicella syndrome (9).…”
Section: Vol 80 2006mentioning
confidence: 99%